Effect of exercise and of prolonged oral administration of propranolol on haemodynamic variables, plasma renin concentration, plasma aldosterone and c-AMP - Bonelli, J; Waldhäusl, W; Magometschnigg, D; Schwarzmeier, J; Korn, A; Hitzenberger, G (European journal of clinical investigation, 1977)
The effect of submaximal exercise upon haemodynamic and biochemical variables was investigated in healthy male subjects, aged 17-27 years, before and at the end of 2 weeks treatment with propranolol (40 mg p.o., q.i.d.). Propranolol reduced the resting blood pressure in normal subjects significantly. This effect was due to reduction of cardiac output and of systemic vascular resistance. No effect of propranolol on BP was seen during maximal exercise, since a reduced cardiac output was accompanied by an increased peripheral resistance. The reduction of cardiac output during exercise can be compensated in part by an increase in stroke volume. The sympathetic activity induced by physical exercise in normotensives increased plasma renin concentration (PRC) and plasma aldosterone (PA), and suppressed urinary excretion of c-AMP. PRC returned to basal levels after 45 min. No increase of PRC was observed after exercise in subjects treated with propranolol. Yet the increase of PA was not completely suppressed. No direct relation was demonstrated between PRC and the haemodynamic variables before or during the administration of propranolol.